Isyarat Sentuhan Antena Semut (Dolichoderus Sp) Pada Tubuh Aphid (Aphis Sp) Untuk Memperoleh Embun Madu - Yayan Sunjaya; Harry Buana; Mimi Halimah (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2009)
Ant, Dolichoderus sp, interact mutually with aphid (Aphis sp).  The ants specifically communicate with the aphid by means of antennal sign.  A hungry ant will approach an aphid and touch it dorsal part using ant antennae; in respond to this, will expel honey dew.  To further study the pattern of communication between the ant and the aphid, their movement was recorded using Handycam JVC GR-SXM 300 AC.  The records were processed using Adobe Premier Pro 1.5.  The results showed that the ant antennae moved in a specific pattern which could be classified into 4 main steps.     The first step consisted of 8 movements which formed 2 movement patterns.  The second step consisted of 3 main repeated movements.  The third step consisted of 3 main repeated movements.  The fourth step consisted of 6 main movements which were repeated several times before the final movement.  Such pattern of antennae movement was recognized by the aphid as tactile signal of ant identity.